The Effect of Finfluencer Credibility on Millennial Investment Decisions: The Moderating Role of Digital Financial Literacy - Dheri Febiyani Lestari dheri; Rina Madyasari; Untung Eko Setyasari; Viska Putria Ananda (POLITEKNIK LP3I, 2026)
The goal of this study is to analyze the results of finfluencers credibility on millennials' investment choices, with digital financial literacy as a moderator. In this analysis, a quantitative explanatory method was used. The sample was millennials with investment experience, using a criterion-based sampling approach. The information was collected using a Likert-scale survey tool, and PLS for SEM was used for processing. The findings demonstrated that finfluencer credibility significantly and favorably influenced investment choices, meaning that the higher the credibility, the greater the probability that individuals will adopt investment recommendations. The impact of digital financial literacy was detrimental and substantial, suggesting that when making financial decisions, those with high reading levels are typically more logical and less impulsive. In addition, Finfluencer credibility and investment decisions were negatively affected by digital financial knowledge, indicating that higher literacy weakens the influence of finfluencers. These findings indicate that millennials' investment decisions are influenced by external factors in the form of information credibility and internal elements as a control mechanism for information filtering, such as digital financial literacy.